2004
DOI: 10.1002/ana.20159
|View full text |Cite
|
Sign up to set email alerts
|

Persistent NKH with transient or absent symptoms and a homozygous GLDC mutation

Abstract: Three of four nonketotic hyperglycinemia patients homozygous for a novel GLDC mutation (A802V) were treated by assisted respiration and/or sodium benzoate with or without ketamine and had transient neonatal or absent symptoms and normal developmental outcome, despite persisting biochemical evidence of nonketotic hyperglycinemia. This exceptional outcome may be related to the high residual activity of the mutant protein (32% of wild type) and therapeutic intervention during a critical period of heightened brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 15 publications
4
47
1
Order By: Relevance
“…Consanguinity in this population is common and has been estimated at $33% of all marriages (Jaber et al 2000). Interestingly, DNA analysis of another family from a different area near Jerusalem revealed another causative mutation (Korman et al 2004). Thus, based on the theoretical calculations presented previously (Zlotogora et al 1996), it may be surmised that the mutation reported here occurred around five generations ago.…”
Section: Discussionsupporting
confidence: 53%
“…Consanguinity in this population is common and has been estimated at $33% of all marriages (Jaber et al 2000). Interestingly, DNA analysis of another family from a different area near Jerusalem revealed another causative mutation (Korman et al 2004). Thus, based on the theoretical calculations presented previously (Zlotogora et al 1996), it may be surmised that the mutation reported here occurred around five generations ago.…”
Section: Discussionsupporting
confidence: 53%
“…In general, the presentation in the atypical neonatal form is similar to the classic neonatal form with hypotonia and apnoeic episodes but the outcome is significantly better [7] and rarely completely normal development has been reported [8].…”
Section: Discussionmentioning
confidence: 92%
“…Broadly based on the age of initial presentation they can be divided into 3 main types: Neonatal (0-4 weeks), Infantile (5 weeks to 2 years) and lateonset (beyond 2 years) [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations